The Verbification of Proper Nouns in English - Janar Nata Prasihan; Widyastuti Widyastuti; Slamet Setiawan (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2021)
The verbification of proper nouns is a term that refers to the changing of the proper nouns into verbs. It has a similar term to the denominal verb. As in the word Meghan Markle which is known as the Duchess of Sussex, yet considered as a verb related to her leaving the royal family incident. This study is aimed to reveal the phenomenon of the verbification of proper nouns, the use of the verbified proper nouns, and the etymology of the verbified proper nouns, especially in English. Using content analysis as one of the qualitative methods, the data then could be collected. The result of the study shows that the verbification of proper nouns in English still existed within the conversation which then classified into several types of verbs; agent verbs, instrument verbs, located verbs. There are thirteen verbified proper nouns listed in the agent verbs, eleven verbified proper nouns listed in the instrument verbs, and three verbified proper nouns listed in the locatum verbs. Since this study could only collect a total of twenty-seven verbified proper nouns and three types of verbs, further studies are widely open to be conducted by researchers in the future.